Best Aid to Orthopedics - TK, Pramod; Johari, Ashok N (New Delhi : Jaypee-Highlights Medical Publishers, 2012)
The book is arranged in questions and answers format. Hence, this makes preparation for examinations and easy task. The answers are written in a pointwise fashion. The tables and flow charts make grasping the subject very easy.
1. Orthopedic trauma 2. Anatomy of bone and fracture healing 3. General principles in the treatment of fractures 4. Splints and traction 5. Recent advances in the treatment of fractures 6. Complications of fracture 7. Peripheral nerve injuries 8. A general review of treatment of orthopedic disorders 9. Injuries around shoulder 10. Injuries around elbow 11. Injuries of forearm and wrist 12. Hand injuries 13. Pelvic fracture 14. Injuries ariund the hip 15. Fracture shaft of femur 16. Injuries around the knee 17. Injuries around ankle
Incluye índice
Keywords: MEDICINA; ORTOPEDIA; CIRUGIA